Cryptococcal Sialoadenitis in a Dog - Borges, Olivia Maria Moreira; Alves, Valbério Brito; Carneiro, Rosileide dos Santos; Dantas, Sabrina Barros Araujo; Matos, Rodrigo Antônio Torres; Vaz, Antônio Fernando de Melo; Lacerda Filho, Armando Marsden; de Souza, Almir Pereira (Acta Scientiae Veterinariae, 2016)
Background: Salivary gland diseases in dogs have an overall incidence of 0.3%. Sialocele and sialoadenitis are the most common injuries and are usually caused by infectious diseases, especially of bacterial origin. Currently, Cryptococcus neoformans has not been registered as the etiological agent since fungal participation is unusual. This case report describes a cryptococcal sialoadenitis in a dog. Case: A 1.9-year-old male poodle had a swelling of the right submandibular region, combined with dry cough and snoring that persisted for about 30 days. The dog often walked in the town square, which has pigeons, and was seen eating chicken droppings. The dog was diagnosed with sialoadenitis in the right submandibular salivary gland. The following laboratory tests were performed cytology, fungal culture, blood count, search for hemoparasites, total plasma protein (ppt), alanine aminotransferase dosage (ALT), alkaline phosphatase (ALP), urea (U), creatinine (CREA), Albumin (ALB), total protein (TP), globulin (GLOB) and amylase (AML). In addition, the dog underwent cervical, thoracic and abdominal ultrasound, and cervical x-rays. The cytology results showed fungal sialoadenitis caused by Cryptococcus neoformans. The blood test results evidenced thrombocytopenia and increased ppt, TP, GLOB, and AML. The lungs and heart x-rays results showed no alterations. However, the proximal third of the trachea was displaced ventrally. The abdominal area had no changes, but hypertrophy of the salivary gland was observed, with irregular contour, heterogeneous echotexture, and multiple cavitary areas flled with intraluminal ﬂuid of cellular appearance. The ketoconazole (5 mg/kg/BID/20 days) treatment prescribed led to drug-induced hepatitis. The new treatment with Itraconazole (10 mg/kg/SID/90 days) resulted in complete clinical resolution without any side effect or relapse one year after the treatment. Discussion: Although poodle is not commonly associated with the epidemiology of the disease, this breed seems to be susceptible, as well. The contact with pigeons during the walks was likely the source of infection by C. neoformans, but the ingestion of chicken droppings cannot be discarded. The coughing and snoring resulted from the pharyngeal and tracheal compression, with subsequent activation of the reﬂex. The clinical and laboratory fndings suggest a new infection route by the etiological agent, possibly the opening of the salivary duct located in the sublingual carbuncle. Biopsy or ablation of the affected salivary gland was not necessary, reducing the risk of sepsis and/or death. Hyperamylasemia indicates that AML can be used as a complementary tool to diagnose sialoadenitis. Itraconazole administered for 90 days resulted in complete healing while no side effects or relapse was observed one year after the treatment. Cryptococcus neoformans can affect the submandibular salivary gland and, therefore, cryptococcosis should enter the differential diagnosis list of canine sialoadenitis and sialocele. Itraconazole has been shown to be effective to treat a dog with sialoadenitis caused by Cryptococcus neoformans. Keywords: sialoadenitis, sialocele, cryptococcosis, salivary gland, dog.